The contribution of ethnobotany and experimental archaeology to interpretation of ancient food processing: methodological proposals based on the discussion of several case studies on Prosopis spp., Chenopodium spp. and Cucurbita spp. from Argentina - Capparelli, Aylen (2014)
The purpose of this paper is to discuss recentmethodological advances in Argentinean archaeobotanythat incorporate the use of ethnobotany as an ethnoar-chaeological tool for interpreting ancient food systems inSouth America. This is an integrative paper that takes intoaccount both published and unpublished results. The role ofethnobotany is examined with reference to ethnobotanicaland experimental food processing studies onProsopis,awild food plant, and two cultivated onesChenopodiumquinoaandCucurbitaspp., followed by laboratory exam-inations with microscopy to identify diagnostic changes inplant morphology and anatomy. Experimental materials arethen compared with archaeological specimens to identifydifferent types of ancient food processing, and to makeinferences about prehistoric post-harvest systems. Wedemonstrated that: (a) it was critical for our food pro-cessing studies to achieve the best taxonomical identifica-tion resolution that the plant remains allow; (b) amulti-proxyapproach was highly advantageous; (c) ethnobotani-cal data were crucial to identify food processing pathwaysof individual plants and combinations of them; (d) theunderstanding of commensality in the wider sense of theterm allows us to determine food patterns both in domesticand funerary contexts. These investigations, the first onesof this type in Argentina, constitute a qualitative step in themethodology for this country because they expand ourabilities to interpret the nature of routine plant processingfrom archaeobotanical assemblages, and they are also asubstantial contribution to the development of our disci-pline in general because thetaxadiscussed in this paper aredistributed throughout South America, as well as in otherparts of the world.